An interactive algorithm for large scale multiple objective programming problems with fuzzy parameters through TOPSIS approach - Abo-Sinna, Mahmoud; Abou-El-Enien, Tarek (Yugoslav Journal of Operations Research, 2011)
In this paper, we extend TOPSIS (Technique for Order Preference by Similarity Ideal Solution) for solving Large Scale Multiple Objective Programming problems involving fuzzy parameters. These fuzzy parameters are characterized as fuzzy numbers. For such problems, the ?-Pareto optimality is introduced by extending the ordinary Pareto optimality on the basis of the ?-Level sets of fuzzy numbers. An interactive fuzzy decision making algorithm for generating ?-Pareto optimal solution through TOPSIS approach is provided, where a decision maker (DM) is asked to specify the degree ? and the relative importance of objectives. Finally, a numerical example is given to clarify the main results developed in the paper. This article has been retracted. Link to the retraction 10.2298/YJOR141008034U nema